RETRACTION Palacio, E. S. (2024). Biomecánica de la cadera. Danza clásica técnica en Dehors. Revisión bibliográfica (Biomechanics of the hip. Classical technical dance in Dehors. Bibliographic review). Retos, 60, 1244–1259. https://doi.org/10.47197/retos.v60.108790 - RETOS, RETOS (Retos, 2025)
Palacio, E. S. (2024). Biomecánica de la cadera. Danza clásica técnica en Dehors. Revisión bibliográfica (Biomechanics of the hip. Classical technical dance in Dehors. Bibliographic review). Retos, 60, 1244–1259. https://doi.org/10.47197/retos.v60.108790 Retraction of the article by the editor of the journal. Disagreements between authors.